Does a Single Low Dose Preoperative Intravenous Erythropoietin Affect Postoperative Blood Loss and Transfusion in Elderly Hip Fracture Patients Receiving Intravenous Iron Therapy: A Randomized Controlled Trial - Chavarat Jarungvittayakon (2022)
Background: Combined recombinant human erythropoietin (rHuEPO) and iron therapy significantly reduced postoperative blood loss (PBL) and allogeneic blood transfusion (ABT) in elderly hip fracture (HF) patients. However, the minimum effective rHuEPO dosage and route had not been studied before. Objective: To evaluate the efficacy of single low dose preoperative intravenous rHuEPO on PBL and ABT in elderly HF. Methods: A randomized controlled trial (RCT) in 32 elderly HF underwent surgical intervention was conducted. The patients were randomly assigned to receive a single dose of 10 000 IU rHuEPO (EPO group, n = 16) or placebo (control group, n = 16) on admission. All patients were given 200-mg iron sucrose intravenously for 3 days after admission. Perioperative data, outcome related to PBL, ABT, rHuEPO adverse effects, and functional outcome during 1-year period were collected and analyzed. Results: There was no significant difference in demographic data, postoperative complication, and functional outcome between both groups (P < .05). Total hemoglobin loss (THL) and the number of patients receiving ABT in EPO group (2.1 ± 1.0 g/dL and 12 patients) did not significant differ from those in control group (2.2 ± 0.8 g/dL and 10 patients) (P = .81 and P = .44, respectively). However, EPO group demonstrated a nonsignificant greater in hemoglobin recovery (P = .07) and increase in reticulocyte count (P = .10). Conclusion: Combined single low dose preoperative intravenous rHuEPO with iron therapy does not significantly reduce PBL and ABT in elderly HF compared to who received intravenous iron therapy alone. However, this adjunct rHuEPO may hasten the hemoglobin recovery and helpful for the patients’ outcome.